Coding strategy of the S and M genomic segments of a hantavirus representing a new subtype of the Puumala serotype - Reip, Angela; Haring, B.; Sibold, C.; Stohwasser, Ralf; Bautz, Ekkehard K. F.; Darai, Gholamreza; Meisel, H.; Krüger, D. H. (Archives of virology, 1995)
The hantavirus strain Vranica was previously reported to have been isolated from a bank vole in Bosnia-Hercegovina and associated with the occurrence of hemorrhagic fever with renal syndrome (HRFS) in humans. The complete cDNA nucleotide sequences of the small (S) and medium (M) genomic RNA segments of this virus were determined. Major open reading frames were found in the S and M segment between nucleotide positions 43 and 1341 coding for a polypeptide of 433 amino acid residues and between nucleotide positions 41 and 3 484 coding for 1 148 amino acid residues, respectively. The analysis and the alignment of the nucleotide and the derived amino acid sequences with known sequences of other hantavirus strains demonstrate that Vranica resembles Swedish strains and represents a new virus subtype of the Puumala serotype distinct from the subtypes represented by virus strains CG18-20 and Sotkamo.
Gesehen am 05.09.2024